2016
DOI: 10.1039/c6ee02215d
|View full text |Cite
|
Sign up to set email alerts
|

A p-Si/NiCoSexcore/shell nanopillar array photocathode for enhanced photoelectrochemical hydrogen production

Abstract: We report the rational design and successful preparation of p-Si/NiCoSex core/shell nanopillar array photocathodes for enhanced solar-driven photoelectrochemical hydrogen generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(133 citation statements)
references
References 56 publications
3
130
0
Order By: Relevance
“…Using PECD, other HER catalysts, e.g., MoS x O y , CoMoS x , NiCoSe x , and CoP, have also been reported to couple to different photocathodes for light‐driven H 2 production. In many cases, the catalyst layers are usually directly photodeposited on semiconductor photoelectrodes without introducing an interlayer, and they offer, besides high catalytic activity, good passivation to semiconductors against corrosion given their exceptional electrochemical stability, exhibiting promising bi‐functionality.…”
Section: Strategies For Semiconductor/electrocatalyst Couplingmentioning
confidence: 99%
“…Using PECD, other HER catalysts, e.g., MoS x O y , CoMoS x , NiCoSe x , and CoP, have also been reported to couple to different photocathodes for light‐driven H 2 production. In many cases, the catalyst layers are usually directly photodeposited on semiconductor photoelectrodes without introducing an interlayer, and they offer, besides high catalytic activity, good passivation to semiconductors against corrosion given their exceptional electrochemical stability, exhibiting promising bi‐functionality.…”
Section: Strategies For Semiconductor/electrocatalyst Couplingmentioning
confidence: 99%
“…Impressive HER performance, n-type semiconductor property and good light-harvesting ability of NiFeSe@NiSe|O@CC could also make it an effective cocatalyst and type-II heterojunction candidate when combined with p-type silicon (Si) as a photocathode material for PEC water splitting (Figure 5e). [26] Electrochemical impedance measurements further verify the enhanced carrier transport of NiFeSe@NiSe|O-Si through smaller charge transfer resistance ( Figure S31, Supporting Information). The delivered photocurrent densities of all the samples under light off condition are negligible as seen from Figure 5f.…”
Section: Resultsmentioning
confidence: 77%
“…To highlight the advantage of PEC photosynthesis relative to conventional electrosynthesis,w es ubsequently investigated the electrochemical reduction of maleic acid on heattreated titanium (Ti/TiO 2 ) [22] and lead-two common electrode materials used widely in previous studies with reported Faradaic efficiencies typically in the range of 70-90 %. [12,20] As depicted in Figure 2c,the polarization curves on Ti/TiO 2 and lead exhibited more negative onset potentials of À0.21 Vand À0.30 V, respectively;a nd their potentials required to reach ac athodic current density of 10 mA cm À2 were À0.68 Vand À0.48 V, respectively.T he Si NW photocathode displayed markedly improved performance in solar-assisted maleic acid reduction relative to Ti/TiO 2 and lead.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…125 mL) was collected and characterized by nuclear magnetic resonance (NMR). [12,22] Thev ery high Faradaic efficiency for the quantitative transformation of maleic acid to succinic acid on the Si NW photocathode therefore presents another advantage over conventional electrosynthesis. Based on its concentration in the catholyte,w ec alculated the Faradaic efficiencyf or succinic acid (Figure 2e).…”
Section: Angewandte Chemiementioning
confidence: 99%